Reconstruction of 3D Image for Particles By the Method of Angular Correlations from XFEL Data - (:unkn) unknown (My University, 2016)
The world’s first X-ray Free Electron Laser (XFEL), the Linac Coherent Light Source (LCLS) at the Stanford Linear Accelerator Center (SLAC), is now generating X-ray pulses of unprecedented brilliance (one billion times brighter than the most powerful existing sources), and at the amazing rate of only a few femtoseconds. The first such experiments are being performed on relatively large objects such as viruses, which produce low resolution, low-noise diffraction patterns on the basis of the so called “diffraction before destruction” principle. Despite the promise of using XFEL for the determination of the structures of viruses, the results so far from experimental data present difficulties in working to reconstruct 3D images for the viruses by our method. One of the rare instances in which images are reconstructed from experimental data is the mimi virus work of Hajdu et al. In this present paper, we examine the capabilities of the method that is based on the angular momentum decomposition of scattered intensities, which enables us to overcome common problems such as missing or imperfect data that are inevitable in experiments. This angular momentum decomposition method helps to avoid the effect of a finite beam size, and existing gap size. In addition to the problem caused by the finite panels of detectors used when the data are collected, the effect of noise, curved Ewald Sphere, shot to shot variations of incident X-ray pulse intensities and shots to multiple nano particles are also studied.
Keywords: 3D Image; Angular Correlation; Diffraction Pattern; Experimental Data; Multi Particle Scattering; XFEL